Immunization of Broiler Chickens With a Killed Chitosan Nanoparticle Salmonella Vaccine Decreases Salmonella Enterica Serovar Enteritidis Load - Acevedo-Villanueva, Keila; Akerele, Gabriel; Al-Hakeem, Walid; Adams, Daniel; Gourapura, Renukaradhy; Selvaraj, Ramesh (Frontiers in Physiology, 2022)
There is a critical need for an oral-killed Salmonella vaccine for broilers. Chitosan nanoparticle (CNP) vaccines can be used to deliver Salmonella antigens orally. We investigated the efficacy of a killed Salmonella CNP vaccine on broilers. CNP vaccine was synthesized using Salmonella enterica serovar Enteritidis (S. Enteritidis) outer membrane and flagella proteins. CNP was stable at acidic conditions by releasing 14% of proteins at pH 5.5. At 17 hours post-incubation, the cumulative protein release for CNP was 75% at pH 7.4. Two hundred microliters of PBS with chicken red blood cells incubated with 20 μg/mL CNP released 0% hemoglobin. Three hundred chicks were allocated into 1) Control, 2) Challenge, 3) Vaccine+Challenge. At d1 of age, chicks were spray-vaccinated with PBS or 40 mg CNP. At d7 of age, chicks were orally-vaccinated with PBS or 20 μg CNP/bird. At d14 of age, birds were orally-challenged with PBS or 1×10^7 CFU/bird of S. Enteritidis. The CNP-vaccinated birds had higher antigen-specific IgY/IgA and lymphocyte-proliferation against flagellin (P<0.05). At 14 days post-infection, CNP-vaccinated birds reversed the loss in gut permeability by 13% (P<0.05). At 21 days post-infection, the CNP-vaccinated birds decreased S. Enteritidis in the ceca and spleen by 2 Log10 CFU/g, and in the small intestine by 0.6 Log10 CFU/g (P<0.05). We conclude that the CNP vaccine is a viable alternative to conventional Salmonella poultry vaccines.